Pengaruh Kepercayaan Konsumen dan Persepsi Kualitas Produk terhadap Niat Beli Produk Essentials Baby Studi Merek MOMAMI - Monica Safilla Priadi; Apriyana, Nurliya (JURNAL MANAJEMEN MOTIVASI, 2026)
The baby care product industry in Indonesia continues to grow alongside increasing parental awareness of the importance of safe and high-quality products, making consumer trust and perceived product quality key determinants of purchase intention. This study aims to analyze the influence of consumer trust and perceived product quality on purchase intention toward Essentials Baby MOMAMI products using a quantitative approach. The results indicate that both variables have a positive and significant effect on purchase intention, with a coefficient of determination (R²) of 0.790. Perceived product quality has a more dominant influence than consumer trust; therefore, companies should prioritize enhancing product quality, including ingredient safety, effectiveness, and product appearance.